Oesophageal pressure and respiratory muscle ultrasonographic measurements indicate inspiratory effort during pressure support ventilation. (July 2020) - Umbrello, Michele; Formenti, Paolo; Lusardi, Andrea C.; Guanziroli, Mariateresa; Caccioppola, Alessio; Coppola, Silvia; Chiumello, Davide
Abstract: Background: Bedside measures of patient effort are essential to properly titrate the level of pressure support ventilation. We investigated whether the tidal swing in oesophageal (ΔPes) and transdiaphragmatic pressure (ΔPdi), and ultrasonographic changes in diaphragm (TFdi) and parasternal intercostal (TFic) thickening are reliable estimates of respiratory effort. The effect of diaphragm dysfunction was also considered. Methods: Twenty-one critically ill patients were enrolled: age 73 (14) yr, BMI 27 (7) kg m −2, and P ao 2 / F io 2 33.3 (9.2) kPa. A three-level pressure support trial was performed: baseline, 25% (PS-medium), and 50% reduction (PS-low). We recorded the oesophageal and transdiaphragmatic pressure–time products (PTPs), work of breathing (WOB), and diaphragm and intercostal ultrasonography. Diaphragm dysfunction was defined by the Gilbert index. Results: Pressure support was 9.0 (1.6) cm H2 O at baseline, 6.7 (1.3) (PS-medium), and 4.4 (1.0) (PS-low). ΔPes was significantly associated with the oesophageal PTP ( R 2 =0.868; P <0.001) and the WOB ( R 2 =0.683; P <0.001). ΔPdi was significantly associated with the transdiaphragmatic PTP ( R 2 =0.820; P <0.001). TFdi was only weakly correlated with the oesophageal PTP ( R 2 =0.326; P <0.001), and the correlation improved after excluding patients with diaphragm dysfunction ( R 2 =0.887; P <0.001). TFdi was higher and TFic lower in patients without diaphragm dysfunction: 33.6 (18.2)% vs 13.2 (9.2)% and 2.1 (1.7)% vs 12.7 (9.1)%; P <0.0001. Conclusions: ΔPes and ΔPdi are adequate estimates of inspiratory effort. Diaphragm ultrasonography is a reliable indicator of inspiratory effort in the absence of diaphragm dysfunction. Additional measurement of parasternal intercostal thickening may discriminate a low inspiratory effort or a high effort in the presence of a dysfunctional diaphragm.